Denmark 1:200 000 Færöe Is. (Great Britain. War Office. General Staff. Geographical Section, 1940)
First edition Relief shown by form lines and spot heights. Depths shown by soundings.; "From a Danish map of 1934."; G.S.G.S. 4128 Color; 1:200,000